2003
DOI: 10.1080/10715760310001601047
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of U937 Cells to Heat Shock by Oxalomalate, a Competitive Inhibitor of NADP+-dependent Isocitrate Dehydrogenase

Abstract: Heat shock may increase oxidative stress due to increased production of reactive oxygen species (ROS) and/or the promotion of cellular oxidation events. Cytosolic NADP+-dependent isocitrate dehydrogenase (ICDH) in U937 cells produces NADPH, an essential reducing equivalent for the antioxidant system. The protective role of ICDH against heat shock in U937 cells was investigated in control and cells treated with oxlalomalate, a competitive inhibitor of ICDH. Upon exposure to heat shock, the viability was lower a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies have indicated a decrease in IDH activity after OMA treatment, resulting in reduced plasma triglyceride and cholesterol levels and adipocyte lipoprotein lipase activity, suggesting a possible inhibitory role of OMA in fat accumulation [41]. Apart from its lipid-lowering effects, OMA has several other effects, such as enhanced apoptotic cell death in cancer cells, and an inhibitory effect on the LPS-induced inflammatory response through the induction of intracellular ROS accumulation [42], [43], [44], [45]. However, to the best of our knowledge, there is no information available regarding the effects of OMA on CNV in AMD.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated a decrease in IDH activity after OMA treatment, resulting in reduced plasma triglyceride and cholesterol levels and adipocyte lipoprotein lipase activity, suggesting a possible inhibitory role of OMA in fat accumulation [41]. Apart from its lipid-lowering effects, OMA has several other effects, such as enhanced apoptotic cell death in cancer cells, and an inhibitory effect on the LPS-induced inflammatory response through the induction of intracellular ROS accumulation [42], [43], [44], [45]. However, to the best of our knowledge, there is no information available regarding the effects of OMA on CNV in AMD.…”
Section: Introductionmentioning
confidence: 99%